2016
DOI: 10.1186/s12876-016-0446-z
|View full text |Cite
|
Sign up to set email alerts
|

Faecal short-chain fatty acids - a diagnostic biomarker for irritable bowel syndrome?

Abstract: BackgroundThe diagnosis of irritable bowel syndrome (IBS) relies on symptom-based criteria. A valid and reliable biomarker that could confirm the diagnosis is desirable. This study evaluated the properties of faecal short-chain fatty acids (SCFA) as diagnostic biomarkers for IBS.MethodsTwenty-five subjects with IBS and 25 controls were included in this explanatory case–control study. Stool samples were analysed for SCFA (acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, and isovaleric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 35 publications
2
78
0
6
Order By: Relevance
“…Here we identify one such metabolite, isovalerate, as a potent EC cell stimulus that modulates sensory neurons via EC cell-neural signaling. Although isovalerate accounts for only a minor percentage of total fatty acid metabolites, high levels are toxic and associated with visceral pain and other gastrointestinal disorders, such as post-infectious irritable bowel syndrome (Brierley and Linden, 2014; Farup et al, 2016; Tanaka et al, 1966). EC cells may act as sensors for such potentially harmful dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Here we identify one such metabolite, isovalerate, as a potent EC cell stimulus that modulates sensory neurons via EC cell-neural signaling. Although isovalerate accounts for only a minor percentage of total fatty acid metabolites, high levels are toxic and associated with visceral pain and other gastrointestinal disorders, such as post-infectious irritable bowel syndrome (Brierley and Linden, 2014; Farup et al, 2016; Tanaka et al, 1966). EC cells may act as sensors for such potentially harmful dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs are metabolites fermented by specific anaerobic bacteria from non‐digestible dietary fiber and resistant starches, and they have extensive regulatory functions in the interaction between microbes and hosts . A few studies have shown that SCFAs are associated with IBS; however, whether they are beneficial or harmful remains controversial …”
Section: Introductionmentioning
confidence: 99%
“…11 A few studies have shown that SCFAs are associated with IBS; however, whether they are beneficial or harmful remains controversial. 12,13 In this study, to further investigate the possible role of gut microbiota in stress-induced visceral hypersensitivity, we examined the influence of chronic water avoidance stress (WAS) in rats on the intestinal barrier and bacterial community and function. We also identified stress-associated microbial species and further verified the beneficial effect of Roseburia, a butyrateproducing genus that was significantly reduced in WAS rats, on stress-induced visceral hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…(Taverniti and Guglielmetti, 2014;Rajilic-Stojanovic et al, 2015). In addition, the available scientific literature also describes the significant role played by altered levels of short-chain fatty acids (SCFAs) in IBS (Ringel-Kulka et al, 2015;Camilleri et al, 2016;Farup et al, 2016). For instance, Farup and colleagues proposed that propionate and butyrate may act as discriminatory factors to differentiate healthy subjects from subjects with IBS (Ringel-Kulka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%